Multidimensional Characteristics of Poverty Kabupaten Pasuruan - Rohmadiani, Linda Dwi; Swara, Dewi (International Journal of Global Sustainable Research, 2024)
The poverty rate for Pasuruan Regency in 2021 according to BPS data is 9.70%, this poverty rate is still above the East Java Province poverty rate of 11.4% and the National poverty rate of 10.14%. Multidimensional poverty in Pasuruan Regency is 32% out of 68%, there is no multidimensional poverty. The aim of the following research is to analyze aspects of the causes of multidimensional poverty in Pasuruan Regency in 2023. The sample population in the research is 396 poor families in Pasuruan Regency in 2023 with a degree of error () of 5%. The sampling technique is proportional random sampling. Data collection methods are carried out through questionnaires, observation and documentation. The analysis techniques applied are Alkire-Foster Analysis and Factor Analysis. The research results show that 33% of sub-districts are included in multidimensional poverty. The factors that most influence the multidimensional poverty of Pasuruan Regency in 2023 include cooking fuel and lighting sources.